Leishmaniasis. Issue 10151 (15th September 2018) - Burza, Sakib; Croft, Simon L; Boelaert, Marleen
Summary: Leishmaniasis is a poverty-related disease with two main clinical forms: visceral leishmaniasis and cutaneous leishmaniasis. An estimated 0·7–1 million new cases of leishmaniasis per year are reported from nearly 100 endemic countries. The number of reported visceral leishmaniasis cases has decreased substantially in the past decade as a result of better access to diagnosis and treatment and more intense vector control within an elimination initiative in Asia, although natural cycles in transmission intensity might play a role. In east Africa however, the case numbers of this fatal disease continue to be sustained. Increased conflict in endemic areas of cutaneous leishmaniasis and forced displacement has resulted in a surge in these endemic areas as well as clinics across the world. WHO lists leishmaniasis as one of the neglected tropical diseases for which the development of new treatments is a priority. Major evidence gaps remain, and new tools are needed before leishmaniasis can be definitively controlled.